In vivo studies of 5-arylethenylbenzofuroxans in acute murine models of Chagas' disease - Boiani, Lucia (2008)
5-Arylethenylbenzofuroxan derivatives with high in vitro anti-Trypanosoma cruzi activity were studied in vivo using acute murine models of Chagas' disease. The selected compounds, as pure isomeric forms, 1, 2, 3 and 4, or as equimolecular mixture of geometric isomers, 1:2, 3:4, 5:6 were studied against different T. cruzi strains. Consequently, Tulahuen 2 strain, Colombiana strain (resistant to Nifurtimox and Benznidazole), and two different wild strains, one isolated from the wild reservoir Didelphis marsupialis and another one from Uruguayan patients, were selected. No relevant signs of in vivo toxicity were observed with the benzofuroxans orally administered. Compound 1 and the mixture of isomers 1:2 were the best for treating infection against the four studied strains.